Directory of information technology specialists in the government. (Quezon City IT Resources Research Unit, National Computer Center, 1991)
The directory is an extract from the Database of IT Manpower in Government. It serves as a helpful reference in IT personnel sourcing and in the validation of applicants to IT positions. The directory presents an alphabetical listing of 668 IT specialists in the government as of August 30, 1991. The directory provides the following information: name, present position, date of appointment, educational background, office name, office address, home address and home telephone number. The directory also features 4 indices to help identify IT specialists according to their department/office, plantilla position title, and areas of specialization.
It includes an alphabetical listing of 668 IT specialists in the government as of August 30, 1991. It can be a helpful guide/reference in IT personnel sourcing and in the validation of applications to IT positions.
Keywords: Information, consultants -- Philippines -- Directories; Information scientists -- Philippines -- Directories; Information services industry -- Employees. -- Philippines